Lactate clearance : prognostic mortality marker in trauma patients (2019)
ABSTRACT: Introduction: High lactate values are associated with adverse outcomes in almost all clinical situations, lactate levels above 2 mmol/L are proposed as an early and reliable marker of tissue hypoperfusion, and lactate clearance during treatment has also been proposed during resuscitation as a prognostic factor. Objective: To determine the association between the initial value of lactate and its clearance after 6 and 24 hours in trauma patients with mortality. Materials and methods: A subanalysis of a prospective cohort collected between March 2014 and October 2016 was carried out at the San Vicente Fundación University Hospital (Medellin, Colombia), with trauma patients over 18 years of age. Lactate and clinical variables were measured at admission, at 6 and at 24 hours. The association of lactate levels at admission and clearance with in-hospital mortality was estimated, using logistic regression models. Results: A total of 251 patients met the inclusion criteria, 15.5% died, 45.4% required admission to intensive care, in patients who died the lactate at admission was 4.6 mmol/L (Interquartile range = 2.9–6.9). The adjusted logistic regression model showed that lactate on admission, lactate clearance of 50% (0–24 hours), trauma mechanism, and Sequential Organ Failure Assessment score were independent factors associated with mortality. Conclusion: High values of lactate at admission are associated with greater probability of dying and its clearance is an independent factor of mortality in those who enter with high lactate values.